Racist love : Asian abstraction and the pleasures of fantasy - Bow, Leslie, 1962- (ANIMA (Duke University Press), 2022)
"Leslie Bow traces the ways in which Asian Americans become objects of anxiety and desire, showing how attraction to Asianized objects and images functions as a source of anti-Asian bias and violence."--